2021
DOI: 10.1002/arch.21794
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome reveal the response to Cry1Ac toxin in susceptible Bombyx mori

Abstract: Bombyx mori as a representative in Lepidoptera is an important economic insect in agriculture production. Bacillus thuringiensis (Bt) is a bacterial pathogen in silkworm production. Understanding how silkworm respond to Bt‐toxin can provide guidance to cultivate resistant silkworm strains. Cry1Ac is one type of Bt‐toxin. In current research, Dazao, a susceptible B. mori strain to Bt‐toxin, was treated by Cry1Ac toxin and compared its transcriptome with untreated samples. This analysis detected 1234 differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Therefore, the chitin based bioformulation may act as an effective pesticide against Lepidopterous pests. A prior work revealed that the expression of cuticle proteins were siginificantly induced at 6 h posttreatment of Cry1Ac toxin (Qin et al, 2021). Genes encoding cuticle proteins were induced during B. mori bidensovirus (BmBDV) infection (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the chitin based bioformulation may act as an effective pesticide against Lepidopterous pests. A prior work revealed that the expression of cuticle proteins were siginificantly induced at 6 h posttreatment of Cry1Ac toxin (Qin et al, 2021). Genes encoding cuticle proteins were induced during B. mori bidensovirus (BmBDV) infection (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to HSP70, the importance of HSP60 in insects is much less understood, particularly in response to Bt toxins. Qin et al found that hsp20 , hsp60 , and hsp70 were upregulated in Bombyx mori (Lepidoptera: Bombycidae) following Cry1Ac toxin treatment. Shabbir et al and Xu et al claimed that the expression level of hsp70 in Cry1Ah- and Cry1Ab-resistant Ostrinia furnacalis (Lepidoptera: Pyralidae) strains was higher than that in Cry1Ah- and Cry1Ab-susceptible strains, and Xu et al identified HSP70 as a putative Cry1Ab-binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…For example, transcriptional analysis of M. separata suffering from a podophyllotoxin‐derived insecticidal agent showed that the primary insecticidal mechanism is the wing‐related development pathway (Sun et al, 2011); Genome‐wide transcriptional analysis for two field thiamethoxam‐resistant populations of Diaphorina citri and susceptible psyllids demonstrated that 60s ribosomal proteins, UDP‐gluscoyltransferases, cytochrome c oxidases, CYP, and ABC transporters were upregulated among thiamethoxam‐resistant D. citri (X. D. Chen et al, 2021); a susceptible Bombyx mori strain to Bt‐toxin was treated by Cry1Ac (one type of Bt‐toxin) toxin. Then, the transcriptomes of the treated and the untreated samples were compared, and it was found that five ABC genes, which are known as the transporters of Bt‐toxin in lepidopteran insects, were upregulated in the Cry1Ac treated sample (Qin et al, 2021); The P450s CYP6BB2 , CYP9M9 . and CYP6M11 were found overtranscribed in association with imidacloprid resistance through the combined transcriptomic and genomic data of Aedes aegypti (Zoh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%